Geographic factors influence communities of symbiotic bacterial communities in Aphis gossypii across China's major cotton regions - Alimu, Abulaiti; Gao, Yu; Liu, Jinping; Lu, Yanhui (Frontiers in Microbiology, 2025)
IntroductionAphids are often infected with diverse bacterial symbionts that enhance their ecological adaptation. While geographic factors significantly influence aphid bacterial communities, research on environmental effects on the cotton aphid Aphis gossypii Glover feeding on cotton plants across China's major cotton-growing regions is limited.MethodsThis study examined the influence of geographic factors on the endosymbiotic bacterial community and diversity of A. gossypii by analyzing 58 field samples from 24 locations across China's major cotton-growing regions (2021–2022) using 16S rRNA (V3–V4) high-throughput sequencing.Results and discussionOur results demonstrate that geography is an important factor in shaping the endosymbiotic bacterial composition and diversity of A. gossypii. Among China's three major cotton-growing regions, the Yangtze River Basin exhibited the highest bacterial diversity, followed by the Northwestern Inland Region, and then the Yellow River Basin. Acinetobacter, Lactobacillus, Serratia, and Aeromonas were more abundant in the Yangtze River Basin, with positive correlations observed for Acinetobacter, Serratia, and Aeromonas in relation to annual precipitation. In contrast, Candidatus Uzinura, dominant in southern Xinjiang, displayed negative correlations with precipitation and longitude but a positive correlation with altitude, and this report is the first detection of it in A. gossypii. Buchnera was ubiquitous and negatively associated with both precipitation and temperature, while Arsenophonus showed no significant environmental correlations. These findings highlight the distinct influences of geographic factors on A. gossypii endosymbiotic communities across China's major cotton-growing regions, broadening our understanding of aphid–endosymbiont–environment interactions and offering potential avenues for biocontrol strategies.